A pilot study of risk oversight of audit committees in today's economic environment - LOW, Irving (Institutional Knowledge at Singapore Management University, 2009)
The KPMG Audit Committee Institute (ACI) in collaboration with the Singapore Management University’s School of Accountancy embarked on this study on the state of corporate readiness. The study also looked at ways to improve an organisation’s resilience by enhancing risk management and governance oversight.